Developing Quality Assurance Practices in Moving Oral Translations to Print - Green Ulibarri, Robin (The Bible translator, 2025)
Oral Bible translation (OBT) is an established practice within many Bible translation agencies; at the October 2024 ETEN Summit, the OBT Table reported 976 active global OBT projects (Mathew et al. 2024). Whether some of these language groups will also want a Bible in print is not a question; many are already working to transcribe their oral translations. Some transcriptions have even gone to print and been distributed. Considering these developments, it is not too early for practitioners and thought leaders to consider guiding principles that will lead to quality in reducing oral translations to print. This article examines the rationale for transcribing OBT and presents three case studies, identifying areas for further consideration. Although drawing some preliminary conclusions, the primary purpose of this article is to start a conversation that will continue as practice informs principles, and vice versa.